Recovery from fatigue after cycling time trials in elite endurance athletes - Ducrocq, G. P.; Hureau, T. J.; Bøgseth, T.; Meste, O.; Blain, G. M. (Medicine & Science in Sports & Exercise, 2021)
Introduction We determined the recovery from neuromuscular fatigue in six professional (PRO) and seven moderately trained (MOD) cyclists after repeated cycling time trials of various intensities/durations.